2 answers:
Answer:
All real values, (-∞, ∞)
Step-by-step explanation:
<u>Step 1: Distribute</u>
5y + (86 - y) = 86 + 4y
5y + 86 - y = 86 + 4y
<u>Step 2: Combine like terms</u>
5y + 86 - y = 86 + 4y
4y + 86 = 86 + 4y
<u>Step 3: Subtract 4y from both sides</u>
4y + 86 - 4y = 86 + 4y - 4y
86 = 86
<u>Step 4: Subtract 86 from both sides</u>
0 = 0
Answer: All real values, (-∞, ∞)
Answer:
0
Step-by-step explanation:
Given
5y + (86 - y) = 86 + 4y
Open parenthesis
5y + 86 - y = 86 + 4y
Rearrange the expression
5y - y + 86 = 86 + 4y
4y + 86 = 86 + 4y
Combine like terms
4y - 4y = 86 - 86
0 = 0
0
You might be interested in
The answer to this subtraction is d
Answer:
D
Step-by-step explanation:
You have to use pythagorean theorem to solve this.
Answer:
16 cm
Step-by-step explanation:
- 4 × 4 = 16 cm
I hope this helps!
Answer:
=
1
1
2
Step-by-step explanation:
.
Move ABCD 3 units to the left and 2 units up. (x-3, y+2)